NUDT21 Promotes Tumor Growth and Metastasis Through Modulating SGPP2 in Human Gastric Cancer - Zhu, Yong; Zhang, Rumeng; Zhang, Ying; Cheng, Xiao; Li, Lin; Wu, Zhengsheng; Ding, Keshuo (Frontiers in Oncology, 2021)
Gastric cancer is one of the major malignancies with poor survival outcome. In this study, we reported that NUDT21 promoted cell proliferation, colony formation, cell migration and invasion in gastric cancer cells. The expression levels of NUDT21 were found to be much higher in human gastric cancer tissues compared with normal gastric tissues. NUDT21 expression was positively correlated with tumor size, lymph node metastasis and clinical stage in gastric cancer patients. High level of NUDT21 was associated with poor overall survival (OS) rates in gastric cancer patients. The expression levels of NUDT21 were also much higher in gastric cancer tissues from patients with tumor metastasis compared with those of patients without tumor metastasis. Moreover, forced expression of NUDT21 in gastric cancer cell BGC-823 promoted tumor growth and cell proliferation in xenograft nude mice, and depletion of NUDT21 in gastric cancer cell MKN-28 restrained lung metastasis in vivo. Through high throughput RNA-sequencing, SGPP2 was identified to be positively regulated by NUDT21 and mediated the tumor promoting role of NUDT21 in gastric cancer cells. Therefore, NUDT21 played an oncogenic role in human gastric cancer cells. NUDT21 could be considered as a novel potential target for gastric cancer therapy.